اسهام نظام إحالة المرضى بين المنظمات في تطوير الخدمة الصحية : دراسة ميدانية في دائرة صحة نينوى - د. عادل محمد عبدالله (PROSPECTIVE RESEARCHES, 2023)
Is it Possible to apply patient sending system in different patient health and social conditions? The research aims at providing mathematical forms to calculate the easiness of transmission of patients. These forms represent one dimension of service quality. These forms are used in determining the degree of easiness of transportation which enables the decision maker in the healthcare center to make his decision. These forms represent important addition in developing healthcare services. The research discovered that, in healthcare centers in Ninawa, there is no discrimination in dealing with people; the patients and those who accompany them are treated in the same way. The research gave an important recommendation about cancelling the system of patient sending in case of limitation in movement facilities.